Metode Studi Aqidah dalam Pemikiran Asy’ariyah, Salafi dan Wahabi - Br Rambe, Siti Aisyah; Abdul Karim, Pangulu; Munthe, Hasanuddin; Rasyid Siregar, Fajar; Wardani, Liza (Yayasan Rahmat Islamiyah, 2023)
Indonesia knows various schools of faith, including the Ash'ari, Wahhabi and Salafi schools. The differences between these schools are very significant, where the Asy'ari aqidah classifies twenty attributes of Allah, while the Whabi and Salafi schools divide monotheism into three parts. Tawhid is interpreted as belief in the oneness of Allah swt, or belief that Allah swt is the One God, so that he has no partners. This research method uses a literature review or library research method with a problem solving approach using analysis. This research attempts to collect research data from the literature and uses literature as the main material for analysis. The main reference for this scientific research uses the books Kifayatul Awam and Manhaj Sunnah. The understanding of Asy'ary aqeedah states that there are twenty attributes of Allah, namely Wujud, Qidam, Baqa, Mukhalafatu-lilhawadisi, Qiyamuhu Binafsihi, Wahdaniyah, Qudrat, Iradat, Ilman, Hayat, Sama', Bashar, Kalam, Qadiran, Discipline, 'Aliman, Hayyan, Sami'an, Bashiran, and Mutakalliman. According to the understanding of the Asy'ari creed that Allah has twenty attributes, the twenty attributes are further classified into the Nafisyah attribute, the Salbiyah attribute, the Ma'ani attribute and the Ma'nawiyah attribute. The names of Allah are used to explain a few of the attributes of Allah in Asmaul Husna and these attributes are simplified so that they are simple to remember and easy to understand. Three interrelated concepts of monotheism are Tauhid Rububiyah, Tauhid Uluhiyah, and Tauhid Asma' Wa-sifat.